Mengungkap Kreatifitas Siswa melalui Pembuatan Alat Peraga Sederhana pada Materi Fluida Dinamis Siswa SMA - Ninda Yera Setyo Nainggolan; Sutikno Sutikno; Suharto Linuwih (Jurnal Riset Pendidikan Fisika, 2021)
This study aims to see the level of creativity of students in making dynamic fluid material props. Subjects who were given treatment were 11th-grade students of the 2019/2020 academic year at MA Nudia in Semarang City. The method used is a quantitative method with the instrument used, namely a questionnaire given via Google form. The questionnaire analysis was prepared based on William's creative indicators. These indicators are creative person, creative process, and creative product. The results of the assistance obtained are personal indicators that get creative predicate, indicators that get very creative predicate, creative indicators that get creative predicate, and product indicators that get very creative predicate. Of the four hands, it can ignore that the subject-categorized as very innovative and creative in students can be seen using simple teaching aids on dynamic fluid material.